Immunomodulatory and Antioxidant Activity of Green Grass Jelly Leaf Extract (Cyclea barbata Miers.) In Vitro - Rendi Mahadi; Mustafid Rasyiid; Krisnanda Surya Dharma; Lindia Anggraini; Rahma Nurdiyanti; Tri Rini Nuringtyas (Universitas Gadjah Mada, 2018)
Green grass jelly (Cyclea barbata Miers.) is known for its benefit to human health especially in supporting body’s immune system and wellness. This research aimed to determine immunomodulatory and antioxidant activity of green grass jelly leaf extracts in vitro. Old leaves were collected as sample then dried and ground to powder. The extraction was done with sohxletation using three different solvents, chloroform, ethyl acetate, and ethanol. The immunomodulatory activity was evaluated by treating the crude extracts at concentrations of 50, 100, and 500 mg/mL on macrophages of rat in vitro. Macrophage cells separated form peritoneal fluid used RPMI medium. Phagocytosis activity and phagocytosis capacity of macrophages were performed in vitro using latex beads that suspended in phosphate buffered saline (PBS). The antioxidant activity was measured by spectrophotometry technique with 1,1-diphenyl-2-picrylhydrazyl (DPPH) solution. All treatments were done three replicates. Detection of the bioactive groups of the extracts was done by Thin Layer Chromatography (TLC). The results showed that ethyl acetate extract has the highest phagocytosis activity followed by chloroform extract and ethanol extract, respectively. Optimum concentration was reached at 100 mg/mL of ethyl acetate extract. The ethyl acetate extract was also the highest antioxidant activity index 7.7 followed by both extracts of chloroform and ethanol similar index value of 6.25 and 6.3, respectively. The ethyl acetate extract has a high immunomodulatory activity and antioxidant activity which contained phenolics, flavonoids, tannins, and terpenoids.